2020
DOI: 10.1038/s41598-020-75977-8
|View full text |Cite
|
Sign up to set email alerts
|

3D rainbow phononic crystals for extended vibration attenuation bands

Abstract: We hereby report for the first time on the design, manufacturing and testing of a three-dimensional (3D) nearly-periodic, locally resonant phononic crystal (PnC). Most of the research effort on PnCs and metamaterials has been focused on the enhanced dynamic properties arising from their periodic design. Lately, additive manufacturing techniques have made a number of designs with intrinsically complex geometries feasible to produce. These recent developments have led to innovative solutions for broadband vibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 54 publications
0
11
0
1
Order By: Relevance
“…Dabei steht meist im Fokus möglichst gute Vibrationsdämpfungseigenschaften zu erzeugen, etwa durch speziell entwickelte Zellen [12,30]. Des Weiteren werden Zellen dahingehend ausgewählt und ausgelegt, dass sie möglichst große Bandbreiten an Schwingungen dämpfen, u. a. durch resonante Phononische Kristalle (PnC) [31] und Topologieoptimierung von Gitterstrukturen [32]. Eine weitere Möglichkeit, die Schwingungsabsorptionseigenschaften zu verbessern, sind eine gezielte Auslegung auf die Absorption von Eigenfrequenzen im System [33] und das Verschieben der Struktur-Eigenfrequenz in einen möglichst hohen Frequenzbereich [34,35].…”
Section: Schwingungenunclassified
“…Dabei steht meist im Fokus möglichst gute Vibrationsdämpfungseigenschaften zu erzeugen, etwa durch speziell entwickelte Zellen [12,30]. Des Weiteren werden Zellen dahingehend ausgewählt und ausgelegt, dass sie möglichst große Bandbreiten an Schwingungen dämpfen, u. a. durch resonante Phononische Kristalle (PnC) [31] und Topologieoptimierung von Gitterstrukturen [32]. Eine weitere Möglichkeit, die Schwingungsabsorptionseigenschaften zu verbessern, sind eine gezielte Auslegung auf die Absorption von Eigenfrequenzen im System [33] und das Verschieben der Struktur-Eigenfrequenz in einen möglichst hohen Frequenzbereich [34,35].…”
Section: Schwingungenunclassified
“…A number of recent studies on mechanical metamaterials [1][2][3][4][5][6][7][8][9][10] with full acoustic bandgaps have attracted intense interests. These materials provide opportunities to precisely control propagations of mechanical waves and have a broad range of potential applications in vibration isolation, 11 acoustic cloaking, 12 wave filters, 13,14 waveguides 15,16 and mechanical switches.…”
Section: Introductionmentioning
confidence: 99%
“…Beli et al [54] proved that the spatial correlated variability could lead to widened bandgaps for cantilever-in-mass metamaterials. Meng et al [55][56][57][58][59] investigated rainbow metamaterial beams with spatially varying oscillators and rainbow phononic crystal lattices with spatial varying mass blocks and found that the rainbow structures could generate broader bandgaps compared with periodic ones.…”
Section: Introductionmentioning
confidence: 99%